Ochrona konsumentów – odbiorców paliw i energii w świetle regulacji art. 6b-6d ustawy Prawo energetyczne (Zagadnienia wybrane) - Mitas, Magdalena (Kwartalnik Prawa Publicznego, 2015)
On the 9th of November 2013 r. came into force the provisions of the Novel to the Polish Energy Law Act, which implement the Directives 2009/72/EC and 2009/73/EC with respect to the protection of energy consumers. The above mentioned changes to the Energy Law ACT give rise to the recognition, that apart of the introduction of general rules providing consumer protection in Energy Law Act, the application of these rules determines the necessity of simultaneous application of the general provisions of the Polish Civil Code regarding notification, the interpretation of wills or legal form. It should be noted that despite the absence of explicit references – changes in the procedure of quasi-complaint shall be that of consumers in the broad sense, and therefore also of so called “vulnerable consumers”. This position is supported by both the trend towards far-reaching protection of economic interests of consumers, including “vulnerable customers”, which is evident in the ECJ case law, as well as by wording of the Directives.